PENGUASAAN TUGAS PERKEMBANGAN ANAK USIA SEKOLAH DASAR YANG MENGALAMI RETARDASI MENTAL - Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan)
Mental retardation refers to significantly subaverage general intellectual functioning existing concurrently with deficits in adaptive behavior, and manifested during the developmental period. Each developmental period has developmental task, which an individual needs to achieved. Therefore, this article is made to explain the achievement on developmental task of school-aged children with mental retardation. Method used to analyze data is qualitative, explanatory case study. Purposive sampling technique found two (2) school-aged children with moderate mental retardation, as research subjects. Data gathered by using observation, interview, and psychological test (Stanford-Binet and VSMS). The result of this study is that the two subjects both able to achieved the school-aged developmental tasks, with limitations. Developmental tasks related with social interaction and gross motor are relatively achieved, than tasks related with intellectual functioning.